Sintesis Heksa-p-tert-Butilheksaesterkaliks[6]Arena dari p-tert-Butilkaliks[6]Arena - Nasriadi Dali; Abd. Wahid Wahab; Firdaus Firdaus; Maming Maming (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2015)
A research has been done to synthesize hexa-p-tert-butylhexaestercalix[6]arene using p-tert-butylcalix[6]arene as a starting material. The synthesis was carried out by esterifying p-tert-butylcalix[6]arene. Synthesis products were identified and characterized by melting point, TLC, FTIR, 1H-NMR, and 13C-NMR spectrometers. Synthesis products was obtained a white solid powder (68.45% recovery), melting point 349-351 °C, TLC (SiO2, ethanol: ethyl acetate = 1: 1 v/v, Rf = 0.90). The results of the analysis of synthesis products with FTIR, 1H-NMR, and 13C-NMR spectrometer showed that the synthesis products compound is 5, 11, 17, 23, 29, 35-hexakis (p-tert-butyl)-37, 38, 39, 40, 41, 42-hexakis (ethoxy-carbonylmethoxy) calix[6]arene.